Local Community Knowledge of Traditional Antenatal and Postpartum Health Care in Daik Lingga - Annisa Inayaturrahmah Choiri Putri; Junardi Harahap (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
In the midst of the development of science and technology era, local knowledge of the community through the role of traditional midwives in antenatal care and postpartum care is still believed and needed by the community. This study aims to describe local knowledge of the community through the role of traditional midwives in traditional health care during pregnancy and postpartum period in Daik Lingga. This study uses a qualitative method with a descriptive approach. Data collection was carried out using in-depth interview techniques and secondary data sources to support the credibility of primary data sources. Informants were determined based on key informants, namely two traditional midwives in Daik Lingga and three residents of Daik Lingga. The results of the study showed that the source of local knowledge of traditional midwives was obtained through hereditary factors. The process of traditional pregnancy and postpartum period health care is divided into two aspects, namely antenatal care and postpartum care with the aim of maintaining and improving the mother and neonatal health. A series of uses of traditional herbal medicines from various medicinal plants and traditional ritual ceremonies are carried out. The tradition of taboos is also believed by the community. This shows that local community knowledge through the role of traditional midwives is still utilized and needed by the Daik Lingga community in antenatal care and postpartum care.